Pulmonary embolism after successful COVID-19 treatment - Ersan Oflar; Fatma Nihan Turhan Caglar (International Journal of the Cardiovascular Academy, 2020)
The novel COVID-19-related disorders have become a global health problem since the pandemic emerged in China. Herein, we present a case of late pulmonary embolism development after successful COVID-19 treatment. A 45-year-old male was admitted to the emergency department with shortness of breath. He was diagnosed with mild COVID-19 pneumonia 10 days ago which was treated with hydroxychloroquine and oseltamivir for 5 days. He did not receive anticoagulation during this period. His second polymerase chain reaction test for COVID-19 came negative at the day before the second admission. He was diagnosed with pulmonary embolism and received anticoagulation therapy with heparin. COVID-19-related complications appear to still happen after treatment. Hence, follow-up of these patients is essential in order to reduce the burden of COVID-19. Thromboprophylaxis is certainly required during hospitalization. Moreover, the duration of thromboprophylaxis may be extended in some patients.